Best Answer

5f + 60 = 90

90 - 60 = 30

5 * ? = 30

5 * 6 = 30

(5)6 + 60 = 90

Q: How do you do 5f plus 60 equals 90?

Write your answer...

Submit

Still have questions?

Related questions

90 + 90 + 60 = 240

390

30 + 5f = 120 -30 -30 5f = 90 /5 /5 f = 18 Check: 30 + 5 (18) = 120 30 + 90 = 120 120 = 120

The result of the equation - 90 plus 90 plus 60 plus 80, is found as follows; 90 + 90 + 60 + 80 = ( 90 + 90 ) + 60 + 80 = 180 + ( 60 + 80 ) = 180 + 140 = 320 Answer = 320

The result of the equation - 60 plus 90 plus 60 plus 80, is found as follows; 60 + 90 + 60 + 80 = ( 60 + 90 ) + 60 + 80 = 150 + ( 60 + 80 ) = 150 + 140 = 290 Answer = 290

90 + 60 = 150

The result of the equation - 120 plus 90 plus 60 plus 80, is found as follows; 120 + 90 + 60 + 80 = ( 120 + 90 ) + 60 + 80 = 210 + ( 60 + 80 ) = 210 + 140 = 350 Answer = 350

The result of the equation - 110 plus 90 plus 60 plus 80, is found as follows; 110 + 90 + 60 + 80 = ( 110 + 90 ) + 60 + 80 = 200 + ( 60 + 80 ) = 200 + 140 = 340 Answer = 340

The result of the equation - 100 plus 90 plus 60 plus 80, is found as follows; 100 + 90 + 60 + 80 = ( 100 + 90 ) + 60 + 80 = 190 + ( 60 + 80 ) = 190 + 140 = 330 Answer = 330

The result of the equation - 80 plus 90 plus 60 plus 80, is found as follows; 80 + 90 + 60 + 80 = ( 80 + 90 ) + 60 + 80 = 170 + ( 60 + 80 ) = 170 + 140 = 310 Answer = 310

The result of the equation - 70 plus 90 plus 60 plus 80, is found as follows; 70 + 90 + 60 + 80 = ( 70 + 90 ) + 60 + 80 = 160 + ( 60 + 80 ) = 160 + 140 = 300 Answer = 300

The result of the equation - 50 plus 90 plus 60 plus 80, is found as follows; 50 + 90 + 60 + 80 = ( 50 + 90 ) + 60 + 80 = 140 + ( 60 + 80 ) = 140 + 140 = 280 Answer = 280